Pancreaticopleural Fistula Causing Massive Right Hydrothorax and Respiratory Failure - Esther Ern-Hwei Chan; Vishalkumar Girishchandra Shelat (Case Reports in Surgery)
Hydrothorax secondary to a pancreaticopleural fistula (PPF) is a rare complication of acute pancreatitis. In patients with a history of pancreatitis, diagnosis is made by detection of amylase in the pleural exudate. Imaging, particularly magnetic resonance cholangiopancreatography, aids in the detection of pancreatic ductal disruption. Management includes thoracocentesis and pancreatic duct drainage or pancreatic resection procedures. We present a case of massive right hydrothorax secondary to a PPF due to recurrent acute pancreatitis. Due to respiratory failure, urgent thoracocentesis was done. Distal pancreatectomy with splenectomy and cholecystectomy was performed. The patient remains well at one-year follow-up.